2005
DOI: 10.1517/14656566.6.11.1851
|View full text |Cite
|
Sign up to set email alerts
|

Acute adverse reactions associated with angiotensin-converting enzyme inhibitors: genetic factors and therapeutic implications

Abstract: Angiotensin-converting enzyme inhibitors (ACEIs) have been used in the treatment of various cardiovascular diseases. Despite the therapeutic benefits of ACEIs, there are several reported side effects, including chronic cough, angioedema and anaphylactoid reactions. These adverse events cannot be explained by the vasodilatory effects of this group of medications. Preliminary studies have shown that patients with a history of developing these side effects have a lower activity of an enzyme called aminopeptidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Previous studies have demonstrated that APP contributes to the regulation of BK metabolism and that depressor responses to apstatin are exacerbated in the presence of ACE inhibition, an effect correlated with increases in measured concentrations of BK in the plasma ( Kitamura et al , 1999 ). In the present study, we clearly demonstrated the importance of APP in the in vivo degradation of BK, second only to ACE in potency, and furthermore suggest that concomitant inhibition of both enzymes by omapatrilat is probably the primary mechanism responsible for the large depressor response in rats (and subsequent angioedema in patients); a finding consistent with increased susceptibility to angioedema in patients with low APP activity on ACE inhibitor therapy ( Adam et al , 2002 ; Duan et al , 2005 ; Nikpoor et al , 2005 ). Thus, there is a need to develop novel BME inhibitors with better selectivity (for example, no APP inhibitory activity) to ensure patient safety from adverse events mediated by APP inhibition ( Jandeleit‐Dahm, 2006 ).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have demonstrated that APP contributes to the regulation of BK metabolism and that depressor responses to apstatin are exacerbated in the presence of ACE inhibition, an effect correlated with increases in measured concentrations of BK in the plasma ( Kitamura et al , 1999 ). In the present study, we clearly demonstrated the importance of APP in the in vivo degradation of BK, second only to ACE in potency, and furthermore suggest that concomitant inhibition of both enzymes by omapatrilat is probably the primary mechanism responsible for the large depressor response in rats (and subsequent angioedema in patients); a finding consistent with increased susceptibility to angioedema in patients with low APP activity on ACE inhibitor therapy ( Adam et al , 2002 ; Duan et al , 2005 ; Nikpoor et al , 2005 ). Thus, there is a need to develop novel BME inhibitors with better selectivity (for example, no APP inhibitory activity) to ensure patient safety from adverse events mediated by APP inhibition ( Jandeleit‐Dahm, 2006 ).…”
Section: Discussionsupporting
confidence: 76%
“…The study of the inter‐relationship between changes in levels of different autocrine modulators, which can occur independently of changes in plasma concentrations ( Slight et al ., 1999 ), may have important clinical implications. These relate to adverse side effects of commonly used drugs such as ACE inhibitors ( Mann et al ., 2005 ; Nikpoor et al ., 2005 ). Thus, understanding the function and interdependence of autocrine modulators will enable a rational design of treatment strategies for correcting or preventing diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…A more likely explanation is that cases with asthma and ACE‐I‐induced cough, one or more cofactors may have increased risk. Potential cofactors include CHF, bradykinin receptor gene polymorphism, ACE insertion/deletion polymorphism, bradykinin‐induced increase in the sensitivity of the sensorial nerve fibers of the airways, defects of the APP enzyme for the degradation of bradykinin and increased cough reflex sensitivity …”
Section: Discussionmentioning
confidence: 99%